Avaliação de marcadores citogenéticos e moleculares relacionados com instabilidade genômica em indivíduos infectados com os vírus das hepatites B ou C - Leite, Samantha Therezinha Almeida Pereira (2011)
Viral hepatitis (B and C) are a major cause of chronic liver disease in the world, and represents an important public health problem worldwide, in Brazil and in the Mato Grosso State. The chronic viral hepatic infection determines an inflammatory process, which produces oxidative stress, a potential inductor of DNA damage, leading to genomic instability, characterized by the presence of chromosomal aberrations (CAs) and micronucleus (MNs). Cellular response to DNA damage by the virus can be influenced by gene polymorphisms related to genomic stability, such as those involved in DNA damage repair. Polymorphism in genes involved in DNA damage repair, such as XRCC1 gene, which participates on the base excision repair (BER), responsible for repairing oxidative damage and polymorphisms in genes involved in the cell cycle maintenance, has been associated with increased risk for development of many diseases, such as cancer. In this context, the present study a) determined the genotipic and alelic frequencies of polymorphism in the genes XRCC1 Arg399Gli and Arg280His and in the gene TP53 Arg72Pro, using PCRRFLP, in patients infected with the hepatitis B (HBV) or C (HCV) virus, compared to non-infected individuals (controls), as well as their association with cirrhrosis, b) assessed the frequency of MN by the cytokinesis-block micronucleus assay in primary cultures of peripheral blood lymphocytes, in vitro, from patients on infected individuals compared to controls and c) associated the frequency of polymorphisms to the frequency of MN. Molecular analysis revealed low frequencies of polymorphism XRCC1 Arg280His in patients when compared to controls, as well as a significant association between the polymorphism XRCC1 Arg399Gli and susceptibility to cirrhosis in patients with HBV or HCV. Results from cytogenetic analysis demonstrated that the frequency of micronucleus was higher in patients than in control group. These results suggests the polymorphism XRCC1 280His does not confer susceptibility to infection by hepatitis B or C and the polymorphism XRCC1 399Gli confers susceptibility to cirrhosis in these patients. Moreover, HBV and HCV patients preset higher genomic instability when compared to controls. However, more studies are needed to investigate these associations.